Amniotic band syndrome: a report of 18 cases - Romero Rojas, Nery (2019)
Amniotic band syndrome is a congenital fetal abnormality characterized by fibrous bands and multiple disruptive anomalies that vary in presentation and complexity, some of which are incompatible with life. We present 18 cases of this syndrome and the associated pathology. Five newborns and 13 fetuses were examined following the standard pathological examination protocol. Nine were males and nine, females, with body weight varying from less than 100 g to 3 680 g. Cases of amniotic bands affected fingers (13 cases), limbs (5 cases), lips (6 cases), face (6 cases), head (6 cases), abdominal wall (2 cases) and umbilical cord (8 cases). Eight cases included associated malformations in heart, lungs, kidneys, gastrointestinal tract, and umbilical cord (single artery, velamentous insertion, short umbilical cord, nuchal cord). Maternal age was 17 to 41 years; 26 years in average. There were 11 primiparous and 7 multiparous women. Five women had a history of previous abortions. The mothers showed no other pathology. In conclusion, fetuses with the amniotic band syndrome present polymorphic and asymmetric anomalies which should be differentiated from those of chromosomal or genetic origin. Ultrasound examination may identify amniotic bands that could be excised, thus releasing the limb or anatomical segment involved.